2019
DOI: 10.1101/696484
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The language network is recruited but not required for non-verbal event semantics

Abstract: Consistent with longstanding findings from neuropsychology, several brain regions in left frontal and temporal cortex respond robustly and selectively to language [1]. These regions, often referred to as the "language network", respond more strongly to meaningful stimuli (like words and sentences) than to stimuli devoid of meaning (like pseudowords and Jabberwocky sentences) [2]. But are these regions selectively recruited in processing linguistic meaning? Or do they instead store and/or process complex semant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 127 publications
(116 reference statements)
2
13
0
Order By: Relevance
“…Although these brain regions, primarily the posterior and temporal cortices, are consistent with previous reports on the modeling of semantic representations (Huth et al, 2012;Nishida et al, 2020a), it may be argued that these regions do not encompass the entire language network, including the left inferior frontal and superior temporal cortices (Friederici and Gierhan, 2013). However, a recent study has clearly demonstrated that language network is not necessarily involved in semantic processing that requires no explicit linguistic processing (Ivanova et al, 2019). They reported that aphasia patients with physical damage to the language network manifested severely declined performance in semantic tasks with linguistic information, but performance equivalent to healthy controls in semantic tasks with nonlinguistic information.…”
Section: Discussionsupporting
confidence: 87%
“…Although these brain regions, primarily the posterior and temporal cortices, are consistent with previous reports on the modeling of semantic representations (Huth et al, 2012;Nishida et al, 2020a), it may be argued that these regions do not encompass the entire language network, including the left inferior frontal and superior temporal cortices (Friederici and Gierhan, 2013). However, a recent study has clearly demonstrated that language network is not necessarily involved in semantic processing that requires no explicit linguistic processing (Ivanova et al, 2019). They reported that aphasia patients with physical damage to the language network manifested severely declined performance in semantic tasks with linguistic information, but performance equivalent to healthy controls in semantic tasks with nonlinguistic information.…”
Section: Discussionsupporting
confidence: 87%
“…In the remaining 484 localizer sessions, participants read the materials passively and performed a simple button-press task at the end of each trial (included to help participants remain alert). The language localizer has been shown to be robust to changes in the materials, modality of presentation, and task (Fedorenko et al, 2010;Fedorenko, 2014;Scott et al, 2017;Ivanova et al, 2019).…”
Section: Participantsmentioning
confidence: 99%
“…Second, to avoid over-inclusiveness, the contrast should not identify functional networks that are distinct from the core language network and might be recruited during online comprehension for other reasons (e.g., task-demands, attention, episodic encoding, non-verbal knowledge retrieval, or mental state inference). Whereas there are many potential differences between the processing of sentences vs. nonwords that might engage such non-linguistic processes, the identified regions exhibit robust language-selectivity in their responses, showing little or no response to non-linguistic tasks (Fedorenko et al, 2011;Fedorenko et al, 2012a;Pritchett et al, 2018;Ivanova et al, 2019;Jouravlev et al, 2019; For a review, see Fedorenko and Varley, 2016). Moreover, these regions are internally synchronized with one another during naturalistic cognition, yet are strongly dissociated from other brain networks (Blank et al, 2014;Paunov et al, 2019; for evidence from inter-individual differences, see: Mineroff et al, 2018).…”
Section: Language Localizer Taskmentioning
confidence: 99%
“…(Unlike previous reports from our group that had used an additional mask in the angular gyrus, we decided to exclude this region going forward because it does not appear to be a part of the core language network in either its task-based responses or its signal fluctuations during naturalistic cognition. See, e.g., Blank et al, 2014;Blank et al, 2016;Pritchett et al, 2018;Ivanova et al, 2019;Jouravlev et al, 2019;Paunov et al, 2019).…”
Section: Functionally Defining Language Regions In Individual Particimentioning
confidence: 99%
See 1 more Smart Citation